Améliorer les pratiques d'enseignement pour favoriser la prise de notes des étudiants - Un accompagnement pédagogique par la recherche-action - Arber Shtembari; Guillaume Gimenes; Nicolas Epinoux; Sophie Haller; Thierry Olive
This study presents the results of an action-research project conducted at the University of Poitiers, with the aim to provide pedagogical support for teaching practices that encourage students' note-taking. The research-action involved a reflective approach by the lecturer based on the results of a questionnaire on note-taking measuring teaching practices. This innovative questionnaire was the central instrument of the support process, making it possible to compare the views of the lecturer and his or her students. The first part of the questionnaire provides information on the teaching methods used by the lecturer during the course; the second part asks the students about their feelings regarding their ability to take notes during a lecture. The pedagogical support contributed in particular to the increase of the lecturer's awareness of certain aspects of his communication during the lecture by enabling him to implement pedagogical methods that encourage his students to take notes. Following this support, the students expressed, through their answers to the questionnaire, that the teacher's new teaching practices had improved their note-taking.